Successful experience in the use of ultrasound elastography in the differentiating of lymphomatous and metastatic superficial lymphadenopathy - E. V. Kovaleva; T. Yu. Danzanova; G. T. Sinyukova; E. A. Gudilina; P. I. Lepedatu; G. F. Allahverdieva; P. A. Zeynalova; V. B. Larionova; I. V. Kolyadina (Онкогематология)
The objective: to evaluate the possibilities of ARFI technology (Acoustic Radiation Force Impulse), including Virtual Touch™ Tissue Imaging (VTI) and Virtual Touch™ Tissue Quantification (VTQ) for differentiation of lymphomatous and metastatic superficial lymphadenopathy.Materials and methods. The prospective study included 138 patients with enlarged superficial lymph nodes (LN). Based on a previous histological examination, patients were divided into two groups: 1st group (n = 108) – patients with non-Hodgkin’s lymphomas and Hodgkin’s lymphoma; 2nd group (n = 30) – patients with metastasis of solid tumors in superficial LN. All patients underwent ultrasound elastography of the enlarged LN using ARFI technology. In VTI study the Area Ratio parameter was evaluated, and the minimum and average values of the shear wave velocity were estimated in VTQ study.Results. According to the results of VTI study the Area Ratio parameter for enlarged LN in lymphoma (1st group) and for metastatic lymphadenopathy (2 nd group) were 1.031 ± 0.197 and 0.851 ± 0.15, respectively (p = 0.000009). The cut off value of the Area Ratio parameter was 0.901 with sensitivity, specificity and accuracy 80.6, 70.0 and 78.8 %, respectively. Minimum values of shear wave velocities for 1st and 2 nd groups were 1.980 ± 0.557 and 2.214 ± 0.367 m/s, respectively (p = 0.032). The cut off values of the average shear wave velocity in the differentiating of lymphomatous and metastatic lymphadenopathy are determined at the level of 2.00 m/s, with sensitivity of 70.0 %, specificity of 59.3 %, and accuracy of 61.6 %.Conclusion. Ultrasound elastography with ARFI technology demonstrated statistically significant differences in the Area Ratio parameter and in the minimum shear wave velocity in the enlarged superficial LN in lymphoma and with metastasis that can be used as a preliminary non-invasive differential diagnosis of enlarged superficial LN in these conditions. Moreover, the Area Ratio parameter has a statistically more significant effect on differentiating of lymphomatous and metastatic lymphadenopathy.